An oral phenylacrylic acid derivative suppressed hepatic stellate cell activation and ameliorated liver fibrosis by blocking TGF‐β1 signalling. (14th December 2022) - Xue, Taixiong; Yue, Lin; Zhu, Guonian; Tan, Zui; Liu, Hongyao; Gan, Cailing; Fan, Chen; Su, Xingping; Xie, Yuting; Ye, Tinghong
Abstract: Background and Aims: Liver fibrosis is an excessive wound‐healing response governed by activated hepatic stellate cells (HSCs). To date, there is no drug available for liver fibrosis. Although ferulic acid (FA) has multiple pharmacological functions, its anti‐hepatic fibrosis activity is weak. Based on the activity modification of the FA structure, we synthesized a series of phenylacrylic derivatives and found a superior compound, FA11. In this study, we investigated its antifibrotic effect and mechanism. Methods: Activated HSC and CCl4 ‐induced mouse liver fibrosis were established and followed by FA11 treatment. Cell viability was measured by CCK‐8 assay. Apoptosis and cell cycle analysis were conducted by flow cytometry. Western blot and Real‐time qPCR were used to examine the expression of fibrotic and M1/M2‐type macrophages markers. Degree of liver fibrosis was shown by histological staining. Results: In vitro, FA11 inhibited TGF‐β1‐induced LX‐2 proliferation and led to apoptosis and cycle arrest. Furthermore, elevation of fibrotic markers in TGF‐β1‐induced LX‐2 and primary activated HSC was reversed by FA11. In vivo, FA11 administration alleviated collagen deposition and blocked HSC activation and epithelial‐mesenchymal transition (EMT). Additionally, FA11 reduced macrophage infiltration in fibrotic liver and prevented macrophage polarization to a profibrotic phenotype. Meanwhile, the systemic toxicity of CCl4 was also ameliorated by FA11. Mechanistically, FA11 reversed the phosphorylation of canonical and noncanonical TGF‐β1 signalling, as well as FGFR1 signalling. Conclusions: We reported an oral phenylacrylic acid derivative, FA11, which showed excellent antifibrotic activity and was expected to be an anti‐hepatic fibrosis candidate. Abstract :